Design and fabrication of a (6.4γ–Al2O3 + 18Al13Fe4)/Al (wt.%) composite utilizing fine grain strengthening and dispersion strengthening at elevated temperatures. (March 2022) - Gao, Tong; Liu, Lingyu; Zhao, Kai; Liu, Shushuai; Han, Mengxia; Liu, Guiliang; Liu, Xiangfa
Graphical abstract: Highlights: A (6.4 γ –Al2 O3 + 18Al13 Fe4 )/Al (wt.%) composite has been in-situ fabricated. The fine grain strengthening and dispersion strengthening at elevated temperatures have been put in use. The composite exhibits attractive mechanical properties at elevated temperature. Abstract: In this work, a (6.4 γ –Al2 O3 + 18Al13 Fe4 )/Al (wt.%) composite (AFO) was in-situ synthesized through the chemical reaction between Al and oxide powders. After hot extrusion, the formed nanometric γ –Al2 O3 particles exhibit networks, locating along matrix grain boundaries. The submicron Al13 Fe4 particles have similar size with the α–Al grains and disperse uniformly among the matrix. It is supposed that the γ –Al2 O3 particles are efficient for grain boundaries stabilization at elevated temperatures, while the Al13 Fe4 particles generate further dispersion strengthening effect. As a result, the AFO composite exhibits attractive high-temperature intensity and heat stability. The yield strength of tensile test at 300 °C is 270 ± 6 MPa, while it can still remain to be 119 ± 10 MPa at 500 °C. It is regarded that this work may provide new insights for designing new Al based composites for elevated temperature applications.